2012
DOI: 10.1021/jp300166h
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Sessile Nanodroplets on Nanopatterned Surfaces

Abstract: Small aqueous droplets on homogeneous surfaces surrounded by a reservoir of vapor are inherently unstable. Depending on the humidity, they keep evaporating and ultimately disappear or grow until they fully wet the surface under supersaturation. We are considering a system departing from this common picture. For nanoscale droplets sitting above hydrophilic patches on a heterogeneous surface, there can exist a range of supersaturated pressures at which the droplets maintain a stable volume, determined by the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 69 publications
5
33
1
Order By: Relevance
“…For a typical case as shown above: the case of a drop of roughly 26 nm in diameter and considering the planar limit of the fluid-vapor tension (72 mN·m . While this number seems to be different from those estimated from micrometer drop experiments [35] or from molecular simulation of atomistic water models [36,37]; it is appropriate to point out that values as low as ×10 −11 J·m −1 and as high as ×10 −5 J·m −1 have been reported [33], which place our results in the correct context. Obviously, there is scope for much more detailed research into this topic.…”
Section: Resultscontrasting
confidence: 82%
“…For a typical case as shown above: the case of a drop of roughly 26 nm in diameter and considering the planar limit of the fluid-vapor tension (72 mN·m . While this number seems to be different from those estimated from micrometer drop experiments [35] or from molecular simulation of atomistic water models [36,37]; it is appropriate to point out that values as low as ×10 −11 J·m −1 and as high as ×10 −5 J·m −1 have been reported [33], which place our results in the correct context. Obviously, there is scope for much more detailed research into this topic.…”
Section: Resultscontrasting
confidence: 82%
“…We suggest that these asymmetries likely originate from molecular properties 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23 while the contact area spans at least 11 nm in the same direction. In view of the work of Ritchie et al, 49 To provide a more direct evidence for the influence of the contact line on the observed asymmetry for pure water, the orientation ordering of the water molecules has been calculated. A similar orientation ordering is found for the 4 M NaCl system (not shown here), indicating that the structure of the water molecules next the co...…”
Section: Resultsmentioning
confidence: 99%
“…They also lead to contact line hysteresis, i.e., the difference between an advancing and a receding contact angle (Neumann et al, 1974;Joanny and de Gennes, 1984;de Gennes, Brochard-Wyart, and Quere, 2004;Quere, 2008;Ramiasa et al, 2013). Indeed, Ramos, Charlaix, and Benyagoub (2003) showed that the amount of contact angle hysteresis linearly increases with the density of defects on nanostructured surfaces (provided it is not too high), due to the pinning-depinning process of the contact line at individual defects.…”
Section: E Origin Of Contact Line Pinning: Surface Heterogeneitiesmentioning
confidence: 99%